Bandwidth enhancement of compact patch antennas by loading inverted “L” and “T” strips - Boukarkar, Abdelheq; Satouh, Rachdi (International journal of microwave and wireless technologies, 2021)
We propose simple designs of compact patch antennas with bandwidth enhancement. Firstly, an inverted “L” strip is loaded onto the corner of one radiating patch edge to create an additional resonant mode which can be combined with that one of the conventional patch to enhance the operating bandwidth. Secondly, the “L” strip is replaced by inverted “T” strip to improve further the bandwidth by creating two adjustable resonant modes. The two proposed patch antennas have the particularity of enhancing the bandwidth significantly without increasing their profile and their overall sizes. Two antenna prototypes are fabricated and tested. Measurements reveal that the patch antenna loaded with “L” strip has stable radiation characteristics with 5.2 times enhancement in the relative bandwidth compared with a conventional patch antenna. The antenna loaded with inverted “T” strip has wider bandwidth (6.25 times wider than the conventional patch) and covers the operating band 5.07–5.89 GHz (15%) with measured peak gain and peak efficiency of 6.25 dBi and 78%, respectively. The proposed antennas are easy to fabricate, have a low-profile, and exhibit good performances which make them good candidates to use in real wireless applications.